Health Promotion Strategy to Prevent Malnutrition Problems in Toddlers - Detriana Imeriet Nenobais; Anastasia Yasintha Thedeens; Monika Bela Zaghu (Sean Institute, 2025)
Toddlerhood is often referred to as the golden age where humans experience rapid growth and development so that optimal nutritional fulfillment is needed. The problem of malnutrition in toddlers is a significant issue in Indonesia, especially in areas with limited access to health services. Mothers' lack of knowledge about nutrition and inadequate parenting patterns are contributing factors to this problem. A good health promotion strategy is needed to help the community in providing good knowledge and understanding to the community to overcome this problem. The purpose of this study was to determine the health promotion strategies by health workers and integrated health post cadres in an effort to prevent malnutrition in toddlers. The study used a qualitative method with in-depth interviews with 7 key informants: health workers, Posyandu cadres, local RTs, and mothers of toddlers at the Melati integrated health post at the Radamata Community Health Center . The results found that the health promotion strategy was implemented through community empowerment, involving Posyandu cadres to provide supplementary feeding to toddlers. A climate-building strategy was also implemented, but was not optimal due to the unconducive educational environment. Advocacy has been conducted with the local government to develop policies to support supplementary feeding through village funds. Partnerships have been established with the local Health Office to help monitor the nutritional status of toddlers at the Posyandu and provide counseling to the community. It was concluded that the health promotion strategy at the Melati Posyandu at the Radamata Community Health Center has been implemented, but has not been optimally implemented.